(untitled) (Economics and region, 2018)
In the article the strategic approaches to regulation of foreign banking are considered and the optimal approach to the national economy is defined. The owners of banks with foreign capital and their country of origin are analyzed; foreign participation in banking assets is estimated. The indirect and direct impact of other governments and international organizations in the Ukrainian banking system are identified; the increasing of the regulator influence on the financial market due to the share of state banks is investigated. The necessity of the development and implementation of the effective mechanism regulation of the foreign capital drawing into the banking system of Ukraine is proven.